Um modelo para a otimização da cogeração de calor e eletricidade em uma planta industrial - Maria Izabel Correa dos Santos (2014)
The search for energy sources with less cost and less environmental impact has become worldwide constant. Thus, the cogeneration of energy become very attractive and started to be applied in industrial plants of different purposes. This solution has the main advantage of increase the thermoelectric generation systems efficiency. In Brazil, this system is mainly used in chemical and petrochemical industries, sugar and ethanol plants and hospitals. However, the CHP has also become a solution for plants that cant be entirely supplied from the local power system or which need to generate heat for the industrial processes. The Cohabitation of the CHPs with other sources of thermal and electrical energy in industrial systems provides a huge number of alternatives to supply the plant. The determination of the lowest-cost alternative can bring significant cost saving to the process. This work presents the optimization of the power generation in systems with cogeneration units working in parallel to the electrical system and other heat sources to supply heat and power in the industrial plants. The development of a cost model for these systems and a case study of a plant with these characteristics.